Highly Efficient Multicomponent Gel Biopolymer Binder Enables Ultrafast Cycling and Applicability in Diverse Battery Formats - Ding, Ling; Leones, Rita; Omar, Ahmad; Guo, Jing; Lu, Qiongqiong; Oswald, Steffen; Nielsch, Kornelius; Giebeler, Lars; Mikhailova, Daria (ACS Applied Materials and Interfaces, 2020)
Electrode materials with a high performance and stable cycling have been commercialized, but the utilization of state-of-the-art Li-ion batteries in high-current rate applications is restricted because of limitations in other battery components, in particular, the lack of an efficient binder. Herein, a novel multicomponent polymer gel binder (PGB) is presented, comprising the biopolymer chitosan as the host, embedded with the 1-butyl-1-methylpyrrolidinium dicyanamide (PYR14DCA) ionic liquid and the lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) salt. The multicomponent approach leads to carbon black arrangement along well-distributed chitosan chains in the electrodes, forming a highly electronic conductive network. Furthermore, the plasticizing effect of the ionic liquid leads to an enhanced ionic conductivity. As a result, shorter charge-transfer paths are enabled, leading to an exceptionally high rate capability in LiFePO4 and Li4Ti5O12 half cells, up to 50C. LiFePO4||Li4Ti5O12 full cells using the PGB for both electrodes also demonstrated stable cycling at 10C, with an impressively high discharge capacity of 173 mA h·g-1 after 1000 cycles. In addition, freestanding electrodes could also be realized and functioning flexible Li-ion cells were successfully demonstrated. Thus, the novel water-processable binder offers multifaceted advantages, making the approach highly promising for industrial implementation.
CRIS-Team Scopus Importer:2022-04-14
Keywords: biopolymer chitosan; freestanding electrodes; high-rate performance; lithium-ion batteries; polymer gel binder